A COMPARATIVE STUDY OF DIABETIC MACULOPATHY AMONG NON PROLIFERATIVE AND PROLIFERATIVE DIABETIC RETINOPATHY PATIENTS - Dr. Subbulakshmi. S; Dr. Arun Vaidhya. T; Dr. Hamsa. V.S (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Diabetic Retinopathy is due to the microangiopathy changes in the retinal precapillary arterioles, capillaries and venules. Diabetic Maculopathy is the leading cause of blindness in Diabetic Retinopathy. Retinal ischemia and edema are the two major intraretinal components of Diabetic Maculopathy. Visual loss is caused by the breakdown of blood retinal barrier, which leads to increase in the extracellular fluid within the retina, resulting in distortion of the retinal architecture. However, Diabetic Retinopathy has an unpredictable evolution and control of this disease is challenging. Hence, with timely detection and treatment, proper follow up and Diabetes Mellitus care, visual loss can be prevented. This study is done to compare Diabetic Maculopathy among Non-Proliferative and Proliferative Diabetic Retinopathy patients. Thus, leading to early treatment and prevention of blindness due to Diabetic Maculopathy. Objective: Comparison of Diabetic Maculopathy among Non-Proliferative and Proliferative Diabetic Retinopathy in Type 2 diabetic patients. Methodology: Non-Proliferative and Proliferative Diabetic Retinopathy patients were prospectively enrolled. All the participants in the study were interviewed using a wellstructured proforma. Patient’s details including age, sex, type and duration of diabetes, treatment history were recorded. Complete Ocular examination was done including Best corrected visual acuity (BCVA), Anterior segment examination using Slit lamp Retinoscopy, Intraocular pressure measurement using Applanation Tonometer, Amsler Grid, Posterior segment examination includes dilated fundus examination with indirect Ophthalmoscope and Slit lamp biomicroscopy using +90D. Fundus Photography will be taken for documentation using canon fundus camera. Statistical analysis was performed using SPSS software. Results: This prospective study was conducted in the Department of Ophthalmology at Vinayaka Missions Medical College, Karaikal. On approval by ethical committee, 100 Diabetic Retinopathy patients were recruited after obtaining informed consent. According to ETDRS Classification patients were recruited in two groups. 50 patients were in non-proliferative and 50 patients were in proliferative Diabetic Retinopathy group. The maximum number of patients belonged to the age group of 51-60 years ie.34 patients (68%) in NPDR Group and 61-70 years ie.21 patients (42%) in PDR group. Females outnumbered males i.e. 26 patients (52%) in NPDR group and 30 patients (60%) in PDR group. The results of the study showed that 21 patients (68%) in NPDR Group had developed Diabetic Maculopathy when compared to PDR Group ie.10 patients (32%) and which was found to be statistically significant. The results of the study also showed that within NPDR group, severe NPDR patients i.e. 10 patients (47%) developed Diabetic Maculopathy when compared to Mild and Moderate NPDR patients. Conclusion: The results of the study showed that 21 patients (68%) in NPDR Group had developed Diabetic Maculopathy when compared to PDR Group ie.10 patients (32%). The results of the study also showed that within NPDR group, severe NPDR patients i.e. 10 patients (47%) developed Diabetic Maculopathy when compared to Mild and Moderate NPDR patients. Since, the prevalence of Diabetic Maculopathy is increasing nowadays in both NPDR and PDR patients, it is advisable to undergo fundus examinations periodically at regular intervals to detect the Diabetic Maculopathy at the earliest. Early treatment with photocoagulation can stabilize the visual acuity and prevent further visual loss. So, it is recommended that diabetic patients should have regular retinal examinations through a dilated pupil within 3–5 years of diabetes and follow-up yearly.